Profil Pelajar dalam Kurikulum Merdeka Madrasah di Era VUCA - Maimunatun Habibah; Edi Nurhidin (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article aims to reveal the concept of P3PPRA in preparing the nation's generation to face the VUCA era. The research method used in this study is descriptive qualitative with a literature review approach. Three main concepts are a reference for tracking data: the P3PPRA, P3, and VUCA World concepts. This study finds that the concept of Pancasila Student Profile and Rahmatan lil Alamin Student Profile (P3PPRA) is a renewal of character education, which philosophically refers to Ki Hadjar Dewantara's educational philosophy about independent humans. Second, the implementation of the Project for Strengthening Pancasila Student Profiles and Rahmatan lil Alamin Student Profiles (P3PPRA) can be carried out through integrated direct and indirect teaching because P3PPRA is an integrated learning activity and is carried out separately from intracurricular subjects. This study concludes that the concept and implementation of P3PPRA, which accommodates a multidisciplinary approach, is a strategy to prepare students who are adaptive to various rapid and spastic changes in life.